THE USE OF CODE-MIXING BY ONLINE SELLERS ON FACEBOOK PAGE â€œPEKEN ONLINE BULELENGâ€ - Sari, Putu Pande Novita (Jurnal Pendidikan Bahasa Inggris Indonesia, 2020)
This study investigated the phenomena of code-mixing in the language used in social media. This study aimed at describing (1) the kinds of code-mixing produced by online sellers; (2) the online sellers' response towards the use of code-mixing. The data collected through online sellers' comments, captions, status and, hashtags on Facebook. The data were analysed based on the linguistic form of code-mixing by Suwito?s theory and the reasons for the use of code-mixing by Holmes Hoffman's theory. There were five steps in collecting the data, namely (1) opens the Facebook page; (2) screenshots code-mixing sentences; (3) writes code-mixing in the form of a table; (4) reads code-mixing sentences; (5) interviews the online sellers. The result showed that there were 50 code-mixing produced by online sellers. The online sellers frequently produced code-mixing in the form of words as a noun, phrase, adjective, clause, hybrid, repetition word and idiom. Meanwhile, the result of the interview showed that online sellers use code-mixing to get people?s attention, limited words or unknown translation.